A Review On The Concept Of Rasayana(Rejuvenation) - Kaur, Harjeet; Anand, Abhishek; Verma, Suchetta (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is an ancient medical science which is known for its unique fundamental principles. It is a holistic science. It does not merely talks about the treatment of ailments but mulls over the complete health of the individual. For healthy person the Rasayana (Rejuvenation) plays important rule to maintain the health. Rasayana is the therapy which is applied to promote long life with good health, strong memory, perfect health, youthfulness, bright complexion and color, bold voice and magnanimity, increase of strength of the body and the sense organs, perfection in speech, sexual power and brilliance. 1It is also the best way to restore the Rasa and other all Dhatus in excellent condition.2